179k views
0 votes
Simplify the expression. the quantity x to the three halves power end quantity to the power of 6

User Wentz
by
6.2k points

2 Answers

0 votes

Answer:


x^9

Explanation:

We are given that an expression


\left\{(x)^{(3)/(2)\right\}^6

We have to simplify the given expression

In order to simplify the expression we will use given below rule

We know that
(a^b)^c= a^(b\cdot c)

Using this rule


(x)^{(3)/(2)\cdot 6}


(x)^(3\cdot 3)


x^9


\left\{(x)^{(3)/(2)\right\}^6=x^9

User Mr Mo
by
6.4k points
7 votes

Answer:

x^9

Explanation:

The rule of exponents that applies is ...

(a^b)^c = a^(b·c)

For your problem, you have a=x, b=(3/2), c=6, so ...

(x^(3/2))^6 = x^(3/2·6) = x^9

User Grimm The Opiner
by
6.8k points